Lipase Immobilized Methacrylate Polymer Monolith Microreactor for Lipid Transformations and Online Analytics. (23rd September 2012) - Mugo, Samuel M.; Ayton, Karl
Abstract: This communication entails development of a facile continuous flow lipase immobilized poly(glycidyl methacrylate‐ co ‐ethylene dimethacrylate (poly(GMA‐ co ‐EDMA)) monolith microreactor for application in lipid transformations. Candida antarctica lipase B was covalently immobilized on poly(GMA‐ co ‐EDMA) monolith prepared in a 700‐μm (internal diameter) silica capillary. The specific activity of the immobilized lipase was calculated to be 30 ± 0.03 U/mg, where U refers to μg p ‐nitrophenol generated/min from 3.5 mM p ‐nitrophenyl butyrate solution. The microreactor performance was further tested for synthesis of lauryl laurate via esterification. Conversions of up to 97 % were realized at a flow rate of 10 μL/min of a mixture of 0.1 M in both lauric acid and lauryl alcohol. These microreactors could be reused at least 15 times over a 1 month time period, stored at room temperature, with minimal to no reduction in the activity of the enzyme. We have also demonstrated microreactors to be useful for facile transesterification of castor oil triglycerides with online ESI–MS analytics key in lipidomics applications.